2014
DOI: 10.1021/sc5000072
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal-Doped Polyaniline/Single-Walled Carbon Nanotubes Nanocomposites: Efficient Electrode Material for High Performance Supercapacitors

Abstract: The demand for superior energy storage devices, such as supercapacitors, has been growing to meet the application requirements of hybrid vehicles and renewable energy systems. Here, we report a simple method to synthesize manganese chloride (MnCl2)-doped polyaniline (PANI)/single-walled carbon nanotubes (SWCNTs) nanocomposites for electrochemical supercapacitors. The possible interactions between MnCl2 and both PANI and SWCNTs was studied by Fourier transform infrared spectroscopy (FTIR), UV–visible spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(45 citation statements)
references
References 50 publications
(72 reference statements)
0
44
1
Order By: Relevance
“…Pure PPy shows the granular like morphology, exhibited in Figure 8(a). 49,50 Figure 8(e,f) shows the HRTEM images of Ag-PPy/Gr nanocomposite at different positions. The rough surfaces of Gr also signify the uniform coating.…”
Section: Hrtem Analysismentioning
confidence: 99%
“…Pure PPy shows the granular like morphology, exhibited in Figure 8(a). 49,50 Figure 8(e,f) shows the HRTEM images of Ag-PPy/Gr nanocomposite at different positions. The rough surfaces of Gr also signify the uniform coating.…”
Section: Hrtem Analysismentioning
confidence: 99%
“…The absorption bands appeared at 3,200 and 2,935 cm −1 were assigned to the stretching of N-H group present in aromatic amines. [49] Peaks at ~551 cm −1 and in lower regions indicate the presence of Mn-O bond. At 1,170 cm −1 , the absorption is associated with N=Q=N stretching, where Q represents quinoid ring while the peak at 816 cm −1 corresponds to the C-H bending vibration.…”
Section: Structural and Morphological Studiesmentioning
confidence: 99%
“…Alternatively, the absorption band at 608 nm is red shifted to 615 and 630 nm for poly(An-co-Py) Cu and poly(An-co-Py) Cu CNT nanocomposite, respectively. These peaks shifting phenomenon clearly suggests that there is a strong interaction between the quinoid rings of both PANI and PPy with MWCNTs and also due to doping effect [26,[33][34].…”
Section: Uv -Visible Spectroscopy Analysismentioning
confidence: 91%
“…The increment of electrochemical properties mainly resulted due to several superior properties of SWCNTs and MWCNTs like small size, high conductivity, high stability and high surface area [22][23][24]. It was reported that the doping of conducting polymers by transition metal ions like Cu 2+ , Co 2+ , Mn 2+ , Zn 2+ , and Fe 3+ (works as redox active materials) improves the capacitance and thus enhances the energy density [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation